Managing nuclear knowledge : Proceedings of a workshop on managing nuclear knowledge, Trieste, 22-26 Aug 2005 - International Atomic Energy Agency, Vienna (Austria); International Center for Theoretical Physics, Vienna (Austria) (Vienna (Austria), 2006)
Sumario (En)
Ilus.; 170 ref. A este texto pertenece CD P05 I61
Keywords: ENERGIA NUCLEAR; RECURSOS ENERGETICOS; PROYECTOS DE DESARROLLO; ORGANIZACIONES INTERNACIONALES; TRANSFERENCIA DE TECNOLOGIA; PAISES EN DESARROLLO; REUNION